2013
DOI: 10.1038/sc.2012.175
|View full text |Cite
|
Sign up to set email alerts
|

Light touch and pin prick disparity in the International Standard for Neurological Classification of Spinal Cord Injury (ISNCSCI)

Abstract: Study design: Retrospective review. Objectives: The International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) assesses cutaneous sensibility through light touch (LT) and sharp-dull discrimination, referred to as pin prick (PP). This project aimed to confirm a tendency for LT to score higher than PP in SCI subjects and discuss possible reasons for such disparity. Setting: Single site cohort study, the London Spinal Cord Injury Centre, United Kingdom. Methods: A retrospective analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Interestingly, higher LT than PP scores were recently reported for a nonspecific cohort of SCI patients, irrespective of the type of injury and the neurological level. 41 The authors attributed this imbalance to the complexity of PP versus LT examination, because the former involves sharp/blunt discrimination and also to a greater susceptibility of spinothalamic than dorsal column axons to damage during SCI. Other studies however, did not find evidence for such an imbalance, showing comparable damage to both the spinothalamic and dorsal column systems in CP.…”
Section: The Sensory Profile Of Cp; Indication On Its Mechanismmentioning
confidence: 98%
“…Interestingly, higher LT than PP scores were recently reported for a nonspecific cohort of SCI patients, irrespective of the type of injury and the neurological level. 41 The authors attributed this imbalance to the complexity of PP versus LT examination, because the former involves sharp/blunt discrimination and also to a greater susceptibility of spinothalamic than dorsal column axons to damage during SCI. Other studies however, did not find evidence for such an imbalance, showing comparable damage to both the spinothalamic and dorsal column systems in CP.…”
Section: The Sensory Profile Of Cp; Indication On Its Mechanismmentioning
confidence: 98%
“…Despite this, it has to be emphasized that SL is determined on the basis of both PP and LT sensations. Although five case scenarios involved clinical reasoning about SL determination, only one scenario showed difference in level between PP and LT. From a retrospective review by Vasquez et al, 12 it is noticed that only in 30.3% instances LT and PP both indicated the same level of injury. Most frequently, PP alone determined the level.…”
Section: Discussionmentioning
confidence: 98%
“…Kang et al [18] also used it to assess the auricular sensation and suggested that it can provide relatively objective and accurate information. The PP test was used to evaluate pain, and it is used in the studies of auricular numbness in parotid gland surgery [15,19,20]. Other sensations were not determined, such as two-point discrimination or temperature sensation.…”
Section: Discussionmentioning
confidence: 99%